Political Developments in the Republic of the Union of Burma until 1948 - يعرب عبد الرزاق عبد الدراجي أ. م. د. (lark, 2021)
The Republic Union of Burma is considered one of the Southeast Asia countries. It is characterized by a unique strategic location. Burma had been governed by many ancient families until it became, in the Eighth Century, the strongest empire in Southeast Asia. It expands reached Thailand and Laos. Burma also had been conquered by the British Empire which looked for Burma as a market for their profitable trade with China and also to secure the Northeast boundaries of their main colony, India. The research aims to shed light on the political developments in Burma and the British rule over Burma, which led to many social, political, and economic changes in this country. The research also includes the efforts of the political movements to obtain independence which took place in 1948. The research was divided into several sections. The first section discusses the geographical location and its strategic importance. The second section includes the development of Burma. The third section discusses the British rule and the concomitant important events including the three British-Burmese wars (1824-1885). The fourth section includes the Japanese occupation of Burma during World War II. Finally, the fifth section discusses the return of the direct British rule to Burma and the efforts of the Burmese nationalists for independence in 1948. The research aims to shed light on the political developments in Burma and the British rule over Burma, which led to many social, political, and economic change in this country. The research also includes the efforts of the political movements to obtain independence which took place in 1948.